What is linguistic creativity in schizophrenia?. (20th November 2021) - Delgaram-Nejad, Oliver; Chatzidamianos, Gerasimos; Archer, Dawn; Larner, Samuel
Abstract : Background: In an experiment in which clinicians were asked to identify formal thought disorder (FTD) in schizophrenia based on writing samples, the mania and creative writing samples received more FTD diagnoses than the FTD samples. We conducted a systematic review to see whether figuration, associated with both schizophrenia and creative uses of language, could contextualize these findings. Methods: This was a systematic review only (PROSPERO ID:116255). We searched AMED, Child Development and Adolescent Studies, CINAHL, MEDLINE, PsycARTICLES, and PsycINFO. Results. Many studies used figuration tasks to test creativity and vice versa, and key factors affecting figurative language output and processing were positive and negative symptom ratios, IQ, and schizophrenia subtype. Discussion/conclusion: Our review suggests that the clinicians in the experiment mentioned above perceived FTD as characterized by linguistic markers of verbal and figural creativity that are impacted by FTD itself. FTD is more likely characterized by expressional disfluencies in specific contexts.